A Study of Onomatopoeia in Wonder Woman Comic - Ni Komang Eka Maheni; Komang Dian Puspita Candra; I Wayan Juniartha (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
This study was about the onomatopoeia words in Wonder Woman Comic. Onomatopoeia is a sound that replicate the sound made by an entity in everyday life. The aims of this study are to find out the types of onomatopoeia words in comic. The data source were taken from the comic entitled Wonder Woman. This study used the theory of onomatopoeia by Elizabeth (2013) to find out the types of onomatopoeia words and also the meaning of onomatopoeia in the comic Wonder Woman. This study used descriptive qualitative method. The data were collected by using observation method and the steps are reading the comic, identifying the onomatopoeia words and taking note the onomatopoeia words. The result of this study show that the types of onomatopoeia that occurred in this comic can be divided into four namely, mechanical, Fast Motion, Animal and Fighting. There are 49 onomatopoeia found in the comic Wonder Woman, and fighting dominantly occurs with 23 data or 46.9% and followed by mechanical 12 data or 24.6%, then animal 8 data or 16.3% and fast motion 6 data or 12.2%. The meaning of onomatopoeia can be classified into contextual and lexical meaning.